Mechanical and flammability properties of PVC reinforced with nano-sized ATH particles - Samat, Noorasikin; Ahmad, Zuraida; Halim, Zahurin; Anuar, Hazleen; Sabaruddin, Fatimah Atiyah (2012)
The effect of nano-sized alumina trihydrate (ATH) as reinforcement and flame retardant in polyvinyl chloride (PVC) were determined. Melt mixing technique using two roll mills was employed to prepare PVC/alumina trihydrate (ATH) nanocomposites with different ATH loadings. The nano-sized ATH particles were treated with silane coupling agent prior to mixing with PVC resin. All the nanocomposites were characterized by flexural, impact and flammability tests. It was found that the addition of nano-sized ATH enhanced the flexural strength of PVC and this property was further increased in treated nanocomposites. However, the impact strength was only improved slightly, excluding the nanocomposite that contains 30phr of treated ATH. The flame retardant property of PVC nanocomposites was also higher compared to pristine PVC.